The Didactic Process in Sacred Baris Dance Performances in Batur Traditional Village: Conservation Strategies Traditional Balinese Art - Pande Putu Yogi Arista Pratama; Muhammad Jazuli; I Wayan Adnyana; Agus Cahyono; Harum Sunya Iswara (Universitas Negeri Semarang, 2022)
Abstrak. The Baris Dance in the Batur Traditional Village of Bali is a sacred dance performed during the Dewa Yadnya ceremony (an offering to the gods), which takes place at the Ulun Danu Batur Temple and its surroundings. The performance of the sacred baris dance is still seen today; this is due to the didactic process that is the basis for preserving the sacred baris dance. The study aimed to analyze the didactic process of performing the sacred baris dance as a strategy for preserving traditional Balinese art. Qualitative research design, with data sources derived from observations, interviews, and documentation. The validity of the data is carried out with triangulation techniques based on the principles of transferability and dependability. In contrast, data analysis includes the didactic process of sacred baris dance performances and strategies for preserving traditional Balinese art. The results of the study include; (1) the form of sacred baris dance performance consisting of 3 parts, namely, papeson (beginning), pangadeng (middle), and pakaad (end); (2) the didactic process in the conservation of traditional Balinese art is derived from knowledge on aspects of tattwa, morals, and ceremonies. The new findings of this study in the correlation between the didactic value in sacred Baris dance performances and the conservation of traditional art found on the island of Bali.